Transitions of poly(dI-dC), poly(dI-methyl5dC) and poly(dI-bromo5dC) among and within the B-, Z-, A- and X-DNA families of conformations - Vorlícková, M; Sági, J (Nucleic acids research, 1991)
It is shown, using circular dichroism spectroscopy, that poly(dI-dC) is capable to isomerize into both Z-DNA and A-DNA in concentrated NaCl + NiCl2 and trifluoroethanol solutions, respectively. This polynucleotide also undergoes a cooperative, two-state transition in ethanol into a structure which most probably is a canonical B-DNA. This implies that the conformation of poly(dI-dC) is unusual in low-salt aqueous solution. The canonical B-DNA is also adopted by poly(dI-methyl5dC) in trifluoroethanol while this polynucleotide adopts Z-DNA not only in NaCl + NiCl2 but also in the presence of MgCl2. Poly(dI-methyl5dC) partially adopts X-DNA in concentrated CsF and mainly ethanolic solutions. Poly(dI-bromo5dC) isomerizes into Z-DNA not only in concentrated NaCl even in the absence of NiCl2 but also in concentrated MgCl2. This polynucleotide transforms between two distinct variants of Z-DNA in ethanol or trifluoroethanol solutions.
Keywords: chlorid sodný; Solutions; Magnesium Chloride; konformace nukleové kyseliny; cirkulární dichroismus; polydeoxyribonukleotidy; Nucleic Acid Conformation; isomerie; roztoky; Circular Dichroism; Isomerism; DNA; Sodium Chloride; Polydeoxyribonucleotides; chlorid hořečnatý